Waste Management System for Food Waste in Western Australia - Hasan, Mahmood (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2023)
Western Australia contributes to the third most waste in a household per annum in Australia. food waste is one of the major causes of climate change and contributes to greenhouse gas emissions. The UN estimates that food waste costs the Australian government up to 20 billion annually. I have been working on a major project to analyse factors that contribute to food waste. Food production, Retail and Consumption are three factors that increase food waste in the developed world.